Application of comprehensive nursing interventions in prevention of deep vein thrombosis after free flap transplantation in patients with oral cancer (综合护理干预降低口腔癌患者皮瓣移植术后深静脉血栓发生率的效果观察) - YU Xiaolin (余晓林) (中西医结合护理)
Objective To investigate the effect of comprehensive nursing interventions in prevention of deep vein thrombosis after free flap transplantation in patients with oral cancer. Methods Totally 132 patients undergoing free flap transplantation followed by radical operation of oral cancer were randomly divided into two groups: 66 cases in the control group received routine care during the perioperative period, and 66 cases in the study group received comprehensive nursing interventions during the perioperative period. The incidence of postoperative deep vein thrombosis of two groups was compared. Results The incidence of postoperative deep vein thrombosis was 7. 58%(5/66)in the study group , which was lower than 21. 21%(14/66) in the control group (P＜0. 05). Conclusion The comprehensive nursing interventions are potentially effective to reduce the incidence of deep vein thrombosis after free flap transplantation in patients with oral cancer. (目的 探讨综合护理干预降低口腔癌患者游离皮瓣移植修复术后深静脉血栓发生率的效果。方法 选取2020年1月—12月行游离皮瓣移植修复术的132例口腔癌患者为研究对象, 随机分成2组。对照组66例患者接受常规护理, 研究组66例患者接受综合护理干预。对比2组术后深静脉血栓发生率。结果 研究组术后深静脉血栓发生率7. 58%(5/66), 低于对照组的21. 21%(14/66), 差异有统计学意义(P＜0. 05)。结论 综合护理干预可以有效降低口腔癌患者游离皮瓣移植修复术后深静脉血栓发生率。)